Penerapan Media Pembelajaran Puzzle Pecahan Untuk Meningkatkan Hasil Belajar Matematika Pada Siswa Kelas IV MI At-Taufiq Semester Ganjil Tahun Pelajaran 2024/2025 - Alya Ghaitsa Zahirashafa; Nur Asyiffa Amalia Yasmin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the implementation of fraction puzzle learning media and analyze its impact on improving mathematics learning outcomes, specifically on fraction material, among fourth-grade students at MI At-Taufiq. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, conducted over two cycles, each comprising planning, action, observation, and reflection stages. The subjects were 20 fourth-grade students. Data were collected through written evaluation tests, observation, and interviews. Results revealed significant improvements: the class average rose from 68 in the pre-cycle to 78 in Cycle I and further to 85 in Cycle II. Learning mastery rates increased from 35% to 70% and ultimately reached 90%. These findings confirm that fraction puzzle learning media is effective in enhancing students' conceptual understanding and mathematics learning outcomes on fraction material.